Sakralisasi Bulan Muharram dalam Tradisi Suro: Studi Ma'anil Hadis pada Masyarakat Desa Sei Muka - Mayzatun Fatma; Sulaiman Muhammad Amir (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The mystification of worship values during the month of Muharram within the Suro cultural tradition remains a persistent phenomenon in the community of Sei Muka Village, Datuk Tanah Datar District, Batu Bara Regency. This study aims to analyze how such mystification emerges through the interaction between Islamic teachings and local cultural practices. Employing a qualitative approach with the living hadith method, data were collected through interviews, observation, and documentation. The findings indicate a shift in the understanding of Muharram from its normative meaning in hadith, emphasizing the enhancement of worship—to a cultural interpretation embedded with mystical elements. Various social prohibitions, such as restrictions on marriage, relocation, and starting new businesses, are believed to carry negative consequences, reflecting the sacralization of time within the community. However, authoritative hadiths concerning the virtues of Muharram do not prescribe such restrictions. This discrepancy demonstrates an expansion of meaning influenced by Javanese traditions and intergenerational cultural internalization. The study concludes that the mystification of worship values represents a dialectical interaction between religious texts and local culture, which shapes distinctive patterns of religious expression while simultaneously indicating a gap between textual and contextual interpretations of hadith